2012
DOI: 10.1002/ijc.27739
|View full text |Cite
|
Sign up to set email alerts
|

A novel RT‐PCR method for quantification of human papillomavirus transcripts in archived tissues and its application in oropharyngeal cancer prognosis

Abstract: Oropharyngeal squamous cell carcinoma (SCC) is strongly associated with human papillomavirus (HPV) infection, which is distinctively different from most other head and neck cancers. However, a robust quantitative reverse transcription PCR (RT‐qPCR) method for comprehensive expression profiling of HPV genes in routinely fixed tissues has not been reported. To address this issue, we have established a new real‐time RT‐PCR method for the expression profiling of the E6 and E7 oncogenes from 13 high‐risk HPV types.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
93
1
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 94 publications
(100 citation statements)
references
References 28 publications
2
93
1
1
Order By: Relevance
“…One Canadian study suggests that high-risk non-HPV16 genotypes were associated with less cervical metastasis and a trend toward better disease-free survival compared with HPV16 types; however, these conclusions were based on only 5 patients with high-risk non-HPV16. 17 In both this article and the study by Gao et al, 16 only a very small number of patients with high-risk non-HPV types were identified, making it difficult to draw conclusions about relative prevalence or clinical behavior.…”
Section: Discussionmentioning
confidence: 89%
“…One Canadian study suggests that high-risk non-HPV16 genotypes were associated with less cervical metastasis and a trend toward better disease-free survival compared with HPV16 types; however, these conclusions were based on only 5 patients with high-risk non-HPV16. 17 In both this article and the study by Gao et al, 16 only a very small number of patients with high-risk non-HPV types were identified, making it difficult to draw conclusions about relative prevalence or clinical behavior.…”
Section: Discussionmentioning
confidence: 89%
“…In their study, the RNAscope HPV-test had a sensitivity of 97% and a specificity of 93% against the reference test, with positive and negative predictive values of 91% and 98%, respectively. Recently, Gao et al 21 have developed a novel qRT-PCR method for quantification of HPV transcripts in archived tissues. They have noted that qRT-PCR and RNAscope HPV-test were 100% concordant in determining HPV status in a series of 45 OPSCC.…”
Section: Discussionmentioning
confidence: 99%
“…A similar study employing a PCR-based approach found that 57 % of tonsillar tumors were positive for HPV16 which represented a significant increase from 1993-1999 to 2006-2011, indicating an increase in total HPV-positive cancers from 25 % to 62 % (P < 0.002) (Nichols et al 2013). RT-qPCR analyses conducted on 150 oral squamous cell carcinoma tissues revealed the presence of HPV in 81.3 % of the samples (Gao et al 2013). Multiplex human papillomavirus genotyping (MPG) is a PCR assay that detects HPV DNA by utilizing a broad-spectrum general primer.…”
Section: Hpv Biologymentioning
confidence: 82%